Integrating Health Literacy into Transformative Pedagogy: An Innovation Model for Primary School Teachers - elinda rizkasari; Prima Trisna Aji (International Journal of Educational Development and Innovation, 2026)
This study aimed to develop and evaluate the Transformative Health-Pedagogy Model (THPM) by integrating health literacy into transformative pedagogy for primary school teachers. Although transformative instructional approaches and health education have been widely discussed, empirical integration of both domains within a structured innovation model remains limited. A sequential explanatory mixed-method design was employed. The quantitative phase used a quasi-experimental pretest-posttest control group design involving 72 primary school teachers in Central Java, Indonesia. The experimental group participated in an eight-week THPM professional development program, while the control group continued regular instructional practices. Quantitative data were analyzed using paired and independent t-tests with effect size calculation. Results indicated significant improvements in teacher innovation readiness and health-pedagogical integration competence in the experimental group, with large effect sizes. The qualitative phase, conducted through interviews and classroom observations, revealed increased pedagogical awareness, adaptive lesson planning, and contextual embedding of health literacy within instructional practice. The findings suggest that integrating health literacy into transformative pedagogy represents a feasible and effective strategy for strengthening instructional innovation in primary education. The proposed model offers a practical framework for aligning pedagogical reform with preventive health development initiatives.